2013
DOI: 10.1093/eurheartj/eht193
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial extracellular volume fraction quantified by cardiovascular magnetic resonance is increased in diabetes and associated with mortality and incident heart failure admission

Abstract: Diabetes is associated with increased ECV. Extracellular volume fraction detects amelioration of ECM expansion associated with RAAS blockade, and is associated with mortality and/or incident hospitalization for heart failure in diabetic individuals. Extracellular matrix expansion may be an important intermediate phenotype in diabetic individuals that is detectable and treatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
246
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(264 citation statements)
references
References 36 publications
14
246
0
4
Order By: Relevance
“…The ECV values in themselves are comparable with those reported in other heart conditions, such as post-myocarditis, cardiomyopathies, diabetic heart and thus it is unlikely that ECV would have any quantitative value in differentiating the post-takotsubo heart from other conditions 38,39 . The real significance of our findings is the striking lack of return to a normal myocardial structure in a condition considered until recently as "a fully reversible form of acute cardiomyopathy".…”
Section: Importance and Extent Of Systolic Diastolic And Extracellulsupporting
confidence: 74%
“…The ECV values in themselves are comparable with those reported in other heart conditions, such as post-myocarditis, cardiomyopathies, diabetic heart and thus it is unlikely that ECV would have any quantitative value in differentiating the post-takotsubo heart from other conditions 38,39 . The real significance of our findings is the striking lack of return to a normal myocardial structure in a condition considered until recently as "a fully reversible form of acute cardiomyopathy".…”
Section: Importance and Extent Of Systolic Diastolic And Extracellulsupporting
confidence: 74%
“…Alterations of the structural properties and intercellular coupling of the myocardium may have occurred with diabetes,52, 68, 69 weakening the electrotonic interaction between myocytes, which acts as a mechanism of suppression of repolarization variability in situ 54, 70. Thus, intervening structural remodeling may have cooperated with reduced Kv currents in promoting the repolarization heterogeneity found in the diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
“…ECV quantification by T1 mapping has significant prognostic implications. Wong et al [40] have demonstrated an association between myocardial extracellular expansion and adverse clinical outcomes using ECV. T1 mapping techniques have another advantage of detecting diffuse fibrosis at early stages of the disease.…”
Section: The Role Of T1 Mapping For Detection Of Diffuse Myocardial Fmentioning
confidence: 99%